Legal protection for personal data security and muzakki financial transactions on digital zakat platform - Insani, Nur; Rohaya, Nizla; Mutiara, Upik; Maguchu, Prosper (Jurnal Hukum Novelty, 2024)
Introduction to the Problem: The implementation of digital zakat has become a popular trend for zakat practices in Indonesia, allowing the muzakki to make their payments swiftly and easily online. However, there are several challenges faced in the adoption of digital zakat in Indonesia, including concerns on the security of personal data and financial transactions. The potentials for hacking or misuse of muzakki's personal data may hinder the development of digital zakat.Purpose/Study Objective: This paper examines the legal protection of the personal data of zakat payers who use digital platforms as the means for distributing their zakat.Design/Methodology/Approach: The method used in this study is qualitative through normative legal research. The data obtained is analyzed with conceptual approach to formulate specific regulations governing digital zakat platform in detail.Findings: The existence of digital zakat is considered a technological innovation that has increased the accessibility of zakat for the people, thereby improving the welfare of those underprivileged. However, confusion and uncertainty regarding the rules and procedures of digital zakat remain in Indonesia. Digitising zakat brings along its own risks and challenges, including the potential for the misuse of funds, data security issues, and the lack of monitoring and accountability. To ensure the appropriate use of zakat funds in accordance with Islamic law and the relevant regulations, both the zakat institutions and the government must strengthen their supervisory and control over the collection and distribution of zakat through digital platforms. Additionally, it is important to note that not all levels of society in Indonesia have access to digital technology. A significant portion of the population, particularly those in remote areas, may not be able to fully participate in digital zakat practices due to lack of internet access or other necessary equipment.Paper Type: Research Article